A new contract on education?: a history of a process - de Puelles Benítez, Manuel (Avances en Supervisión Educativa, 2010)
Manuel Puelles Benítez (Emeritus Professor at UNED) In 1978, a constitutional agreement on education was reached in Spain and, nevertheless, over thirty years later we still carry on talking about the need of a new compromise on education. After locating the contract on education in its historical and political background, this article reveals its meaning throughout time since the 1978 Spanish Constitution came in force, while, at the same time, it takes a practical outlook on the reasons why it is necessary and why it recently failed to be.